Utilization of Video in Indonesian Language Learning in Elementary Schools in Indonesia - Anggraeni, Alviana Dwi; Setiawan, Andika Aji; Rachmawati, Umi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Learning Technology was born from the reality of education and the audio-visualcommunication movement. Learning Technology was originally seen as equipmenttechnology, which was related to the use of equipment, media and means to achieve educational goals or in other words teaching with audio-visual aids. One of the audiovisual-based teaching materials is video. Indonesian Language and Literature subjects are oriented towards the nature of learning Language and Literature which states thatlearning Indonesian is learning to use a good and correct language.This research ismotivated by the problems that occur in learning Indonesian starting from the low level ofconcentration of students, then the difficulty of students in speaking in Indonesian, thedifficulty of students in reading, and then the difficulty of students in writing. This studyaims to determine the effect of using video media on learning outcomes in Indonesianlanguage learning. The attention function of video media can attract attention and directstudents' concentration on video material and the affective function of video media is ableto arouse the emotions and attitudes of the audience. The results of using this video mediain learning are to improve students' abilities in developing students' abilities in usingIndonesian.